Female age is associated with the optimal number of oocytes to maximize fresh live birth rates: an analysis of 256, 643 fresh ART cycles. Issue 3 (March 2021) - Zhang, Ning; Law, Yin Jun; Venetis, Christos A.; Chambers, Georgina M.; Harris, Katie
Abstract: Research question: What is the optimal number of oocytes retrieved at which maximum live birth rate is observed after fresh autologous assisted reproductive technology (ART) cycles for women of different ages? Design: Retrospective cohort study of all fresh autologous ART aspiration cycles ( n = 256, 643) undertaken in Australia and New Zealand between 2009 and 2015. Primary outcome measure was live birth rate (LBR) (delivery of at least one liveborn baby at 20 weeks' gestation or over per fresh aspiration cycle). Cycles were grouped according to female age (<30, 30–34, 35–49, 40–44 and ≥45 years) and ovarian response (one to three, four to nine, 10–14, 15–19, 20–25 and ≥25 oocytes). Secondary outcome was incidence of ovarian hyperstimulation syndrome (OHSS) requiring hospitalization. Results: At different oocyte yields, LBR per fresh aspiration cycle peaked and then declined at, depending on female age: <30 years: six to 11 oocytes (LBR 31–34%); 30–34 years: 11–16 oocytes (LBR 29–30%); 35–39 years: nine to 17 oocytes (LBR 21–24%); and 40–44 years: 15–17 oocytes (LBR 11–12%). The incidence of OHSS increased significantly with the number of oocytes retrieved, from 1.2% with 15 oocytes retrieved to 9.3% with 30 or more oocytes retrieved ( P < 0.001). Conclusion: The optimal number of oocytes at which maximum LBR was observed in a fresh aspiration cycle was highly dependent on age. Because of the observational nature of the results, a cause–effect relationship between the number of oocytes retrieved and LBR should not be assumed; evidence from well-designed randomized control trials is required before clinical advice can be suggested.